-5g-7=3

Simple and best practice solution for -5g-7=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5g-7=3 equation:


Simplifying
-5g + -7 = 3

Reorder the terms:
-7 + -5g = 3

Solving
-7 + -5g = 3

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -5g = 3 + 7

Combine like terms: -7 + 7 = 0
0 + -5g = 3 + 7
-5g = 3 + 7

Combine like terms: 3 + 7 = 10
-5g = 10

Divide each side by '-5'.
g = -2

Simplifying
g = -2

See similar equations:

| -2n-15=61 | | f(x)=x^2+5x-2(2f(2)) | | f(x)=x^2+5x-2 | | 6+10x=42 | | [2-5(6+11)]= | | -4x+9y=-27 | | -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= | | w-8=-2 | | Y=x^2+4x+8 | | 3x*(2x+5)-(x+3)*(3x-1)=1 | | 11z^2+54=36 | | 10x+80=100 | | (3*4)n-9n=39 | | 5.23-(-9.1)= | | X^2=8x-20 |

Equations solver categories